Two new species of Rhopalopsole (Plecoptera: Leuctridae) from Wuyi Mountains of China - Yang, Yu-Ben; Du, Yu-Zhou (Zootaxa, 2021)
Two new species of Leuctridae (Plecoptera) from Wuyi Mountains, Fujian Province of southeastern China, Rhopalopsole wuyishanensis sp. nov. and Rhopalopsole trichotoma sp. nov. are described and illustrated. The new species are compared to the closely related species of the R. dentata group and the R. shaanxiensis group in this genus, respectively.